2009
DOI: 10.1111/j.1539-6924.2008.01193.x
|View full text |Cite|
|
Sign up to set email alerts
|

A Model of Exposure to Rotavirus from Nondietary Ingestion Iterated by Simulated Intermittent Contacts

Abstract: Existing microbial risk assessment models rarely incorporate detailed descriptions of human interaction with fomites. We develop a stochastic-mechanistic model of exposure to rotavirus from nondietary ingestion iterated by simulated intermittent fomes-mouth, hand-mouth, and hand-fomes contacts typical of a child under six years of age. This exposure is subsequently translated to risk using a simple static dose-response relationship. Through laboratory experiments, we quantified the mean rate of inactivation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
107
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(112 citation statements)
references
References 48 publications
3
107
0
2
Order By: Relevance
“…(25) The limited number of models results, in part, from the difficulty in obtaining the detailed activity data needed to generate quantified estimates of contact rates between hands and fomites, hands and mucus membranes, and fomites and mucus membranes. Measurements of contact rates are difficult because of the high frequency and relatively short duration of these activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(25) The limited number of models results, in part, from the difficulty in obtaining the detailed activity data needed to generate quantified estimates of contact rates between hands and fomites, hands and mucus membranes, and fomites and mucus membranes. Measurements of contact rates are difficult because of the high frequency and relatively short duration of these activities.…”
Section: Introductionmentioning
confidence: 99%
“…Although they presented a hypothetical evaluation of their model by estimating the infection risk of influenza A in the workplace, they did not evaluate their model with empirical data. Similarly, Julian et al (2) presented a hypothetical evaluation of the micro-activity approach to assessing risk of rotavirus infection in daycare settings, but they also did not evaluate their model with experimental data. No previous studies were found in the literature reporting estimated pathogen loading on hands from contact with fomites evaluated with real-time environmental sampling.…”
Section: Introductionmentioning
confidence: 99%
“…For estimating non-dietary ingestion exposures, quantified mouthing activity data of children thought to be important 3; 13; 15; 1719 . In particular, these data are often used to estimate soil and/or dust ingestion rates and intake of chemicals from this exposure pathway 20–24 .…”
Section: Introductionmentioning
confidence: 99%
“…Mouthing and hand contact frequencies are key parameters for estimating non-dietary ingestion and dermal exposure (Zartarian et al, 2006;Nicas and Best, 2008;Stapleton et al, 2008;Julian et al, 2009;Schleier et al, 2009;Macedo et al, 2010;Tulve et al, 2010), as well as soil/dust ingestion rates (Ö zkaynak et al, 2010) critical for most hazardous site clean-up risk assessments including Superfund sites (US EPA, 2004). Several studies have quantified these mouthing and hand contact behaviors in children (Zartarian et al, 1997aBrinkman et al, 1999;Reed et al, 1999;Freeman et al, 2001Freeman et al, , 2005Tulve et al, 2002;AuYeung et al, 2004;Black et al, 2005;Auyeung et al, 2006;Beamer et al, 2008); however, we know of only one other study that has reported any data on children over 6 years of age (Freeman et al, 2001).…”
Section: Introductionmentioning
confidence: 99%